A Novel Humanized Anti-Abrin A Chain Antibody Inhibits Abrin Toxicity In Vitro and In Vivo - Peng, Jingyi; Wu, Jiaguo; Shi, Ning; Xu, Hua; Luo, Longlong; Wang, Jing; Li, Xinying; Xiao, He; Feng, Jiannan; Li, Xia; Chai, Lihui; Qiao, Chunxia (Frontiers in Immunology, 2022)
Abrin, a type-II ribosome inactivating protein from the seed of Abrus precatorius, is classified as a Category B bioterrorism warfare agent. Due to its high toxicity, ingestion by animals or humans will lead to death from multiple organ failure. Currently, no effective agents have been reported to treat abrin poisoning. In this study, a novel anti-abrin neutralizing antibody (S008) was humanized using computer-aided design, which possessed lower immunogenicity. Similar to the parent antibody, a mouse anti-abrin monoclonal antibody, S008 possessed high affinity and showed a protective effect against abrin both in vitro and in vivo, and protected mice that S008 was administered 6 hours after abrin. S008 was found that it did not inhibit entry of abrin into cells, suggesting an intracellular blockade capacity against the toxin. In conclusion, this work demonstrates that S008 is a high affinity anti-abrin antibody with both a neutralizing and protective effect and may be an excellent candidate for clinical treatment of abrin poisoning.